Nilai Pembelajaran dari Pemanfaatan Tinggalan Jepang dalam Konsep Open Air-Museum di Situs Kendari II Airfield (Lanud HLO), Konawe Selatan, Sulawesi Tenggara - Sandy Suseno (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This article aims to examine the value of learning from the utilization of the Kendari II Airfield site which is a relic of the Japanese Occupation era through the open air-museum concept. This research is a qualitative research with literature review, data collection through literature study and secondary data search in the form of archive data, maps, and documents related to Japanese remains found on the Kendari II Airfield site. Through the concept of learning that can be classified based on knowledge and understanding, skills, attitudes and values, fun and creativity, activity and behavior, it can be concluded that historical remains at the Kendari II Airfield site which is used as an open-air museum have potential value as one of the alternative in history learning.